Mixing studies in unbaffled stirred tank reactor using electrical resistance tomography - Sardeshpande, Madhavi V.; Kumar, Gaurav; Aditya, T.; Ranade, Vivek V. (Flow Measurement and Instrumentation, 2016)
Unbaffled stirred tanks are extensively used in chemical process industries for variety of applications including semi-batch reactions. In un-baffled stirred tanks, impeller rotation generates a vortex and reactants are added into this vortex. There is a growing interest towards understanding the mixing performance of such unbaffled stirred vessels. The present work is aimed at providing experimental results on mixing time and solid particle distribution inside an unbaffled vessel using electrical resistance tomography (ERT). A methodology for using ERT for characterizing vortex and mixing in unbaffled stirred vessel was established. The ERT was used to measure the mixing time with and without solid particles (glass beads, 250 mu m) in a stirred reactor. In this study, ERT technique was effectively applied for imaging solid-liquid flow and developed suitable data processing methodologies. It observed that estimated liquid phase mixing time for Un-baffled vessel was more as compared to baffled vessel. Radial solid concentration profiles showed Gaussian distribution inside the vessel. The presented methodology of using ERT and experimental results will be useful for designing and estimating mixing and solid distribution in unbaffled stirred tanks. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ERT; Mixing time; Radial solid concentration; Unbaffled stirred tank